(untitled) (Ozone Therapy Global Journal, 2021)
Sporotrichosis is a mycotic, granulomatous infection with subacute to chronic evolution that affects animals and humans. Felines are the ones that represent the greatest source of infection, which affects their potential transmission This work aimed to describe a case of sporotrichosis in a feline treated at a veterinary clinic in the city of São Caetano do Sul, São Paulo, pointing to the characteristics of the lesion such as the diagnosis, treatment and use of ozone therapy as a complementary treatment. . In this case, the drug itraconazole was used for 6 months, and ozone therapy as a complementary treatment using the rectal insufflation technique, and subcutaneous applications of ozone gas in the cervical region and massaging the gas to the region of the lesion, 5 times a week. with 5 consecutive days of applications and 2 days off, totaling 20 applications in 4 weeks, and applications of ozonated sunflower oil daily, twice a day. Ozone therapy with its immunomodulatory effect, activation of the immune system, direct oxidation of microorganisms and residual regeneration, together with clinical treatment, has been shown to be very effective in the treatment of feline sporotrichosis, reducing the healing time of the lesions and decreasing the side effects of allopathic medications when used long term.